Badania ratownicze na wielokulturowym stanowisku Łódź Łaskowice, stan. 27 - Adamczyk, Ryszard; Zawilski, Paweł (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
Excavations conducted in 1999 in Łódź Łaskowice, site 273 were of rescue character. As a result, the western edge of a multicultural settlement complex has been excavated. The area included elements of the Świder culture (late Paleolithic), Trzciniec culture (II and I/III periods of the Bronze Age), Lusatian culture (Hallstatt D), Przeworsk culture (Roman period) and the Middle Ages. Relics of the Trzciniec culture (most of settlement pits, cultural layer, prevailing part of material) were predominant among the distinguished units. Elements typical of its classical development stage - period II of the Bronze Age as well as younger materials representing the declining phase dated to the turn of period II. As regards establishing chronology of the finds, ceramic materials are of great importance. They comprise elements referring to older development period of the Trzciniec culture (bowls, elements of the Otomani culture), which should be recognized as the earliest in the assemblage. The classical Trzciniec culture is represented by typical vessels with thickened rims, decorated with plastic round bands. Determinant of late development phases is, among others, vase form decorated with plastic bow-shaped band placed on the belly. The elements under consideration are dated by numerous analogies from Little Poland to the turn of period II of the Bronze Age. A considerable concentration of Trzciniec culture settlement points has been registered around the discussed site. In period III of the Bronze Age this centre became a starting point of an early phase of the Lusatian culture - Konstantynów group on the upper Ner. The Lusatian culture materials from its declining period (Hallstatt D) appeared on the discussed site, though on a smaller scale. The materials probably correspond to the east-Great-Poland group. The other units that have been distinguished at the beginning of the work have been recorded within the excavated area of the site in scanty amount.